Enhancing Repurchase Intentions: The Role of Product Quality, Service Quality, and Consumer Satisfaction as a Mediator - Alifia, Taarissa Nur; Deviastri, Lily (SAN Scientific, 2025)
This inquires about points to investigate the effect of item quality and benefit quality on repurchase eagerly, with shopper fulfillment serving as a intervening calculate. Information was accumulated through a survey, and the investigation utilized the Fractional Slightest Square Auxiliary Condition Modeling (PLS-SEM) strategy. The discoveries demonstrate that both item quality and benefit quality altogether impact repurchase eagerly through customer fulfillment. Particularly, item quality emphatically and essentially influences repurchase purposefully, as does benefit quality. Furthermore, item quality emphatically and essentially contributes to buyer fulfillment, whereas benefit quality too emphatically impacts buyer fulfillment. Customer fulfillment, in turn, features a positive and noteworthy impact on repurchase eagerly, and it somewhat intervenes the relationship between item quality and repurchase eagerly. So also, shopper fulfillment somewhat intercedes the impact of benefit quality on repurchase eagerly. Administrative Suggestions: This thinks about emphasizing the imperative part of both item quality and benefit quality in improving buyer fulfillment, which eventually drives repurchase eagerly. For supervisors, this underscores the significance of maintaining tall benchmarks in item offerings and benefit conveyance to cultivate client devotion.